Critical Pedagogical Analysis of Permendikdasmen No. 9 of 2025: The Contradiction of Academic Ability Tests (TKA) in the Context of Revitalising Vocational High Schools (SMK) - Hertanto, Yudhi; Hasbullah, Hasbullah (Transpublika Publisher, 2025)
Permendikdasmen No. 9 of 2025 introduces the Academic Ability Test (TKA) as a new standardization and selection instrument in Indonesia's education landscape. This policy aims to provide standardized academic achievement data for selection purposes (Ministry of Education and Education, 2025). This paper presents a critical pedagogical analysis that argues that, in the context of Vocational High Schools (SMK), TKA policies show significant pedagogical dissonance. Using the theoretical lens of constructivism, differential pedagogy, and authentic evaluation, this analysis shows that TKA is philosophically contrary to the basic principles of vocational education. Instead of answering chronic competency gaps, especially soft skills deficits which is consistently identified by the industrial world, foreign workers are at risk of exacerbating the phenomenon of academic drift (shift of focus to academics). Furthermore, TKA creates assessment redundancy (overlapping with ANBK) and paradoxically devalues the significance of performance-based assessments of the Expertise Competency Test/UKK which should be the heart of vocational education. This paper recommends radical differentiation or exclusion of foreign workers for vocational schools, as well as the strengthening of UKK as a 'golden standard' for national vocational assessments that are in line with international best practices.